Two-Stage Global–Local Aerodynamic/Stealth Optimization Method Based on Space Decomposition - Wei Zhang; Lin Zhou; Bowen Shu; Xian Chen; Zhenghong Gao; Jiangtao Huang (Aerospace)
The design of the flying wing airfoil must consider aerodynamic stealth and trim requirements, with their coupling exacerbating the complexity of the design problem by introducing multiple local minimum points in design space. In addition, it would need a broad space with high dimensionality to obtain the ideal result, and expansion of design space could lead to more local minimum points, causing significant challenges to traditional optimization design methods. A Two-Stage Global–Local Constrained Optimization Method (TGLCOM) was proposed to address these issues. The parametric space was divided into a large-scale global space and a high-dimensional local space. A surrogate-based global constrained optimization method was applied in the large-scale global space, followed by a gradient-based algorithm in the high-dimensional local space to refine the design and obtain the global optima. The efficiency and robustness of the proposed TGLCOM were verified through the airfoil and flying wing layout aero/stealth design. The results indicated a minor conflict between the RCS drag and pitch moment performance. Moreover, the stealth design of the airfoil improved the stealth performance of the flying wing layout in both the yaw and pitch directions.